1996
DOI: 10.1074/jbc.271.5.2548
|View full text |Cite
|
Sign up to set email alerts
|

Mimosine Targets Serine Hydroxymethyltransferase

Abstract: The plant amino acid, mimosine, is an extremely effective inhibitor of DNA replication in mammalian cells (Mosca, P. J., Dijkwel, P. A., and Hamlin, J. L. (1992) Mol. Cell. Biol. 12, 4375-4383). Mimosine appears to prevent the formation of replication forks at early-firing origins when delivered to mammalian cells approaching the G 1 /S boundary, and blocks DNA replication when added to S phase cells after a lag of ϳ2.5 h. We have shown previously that [ 3 H]mimosine can be specifically photocross-linked both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…We estimate that the cSHMT protein accounts for approximately 25% of the total SHMT activity in MCF-7 cells. 3 The addition of 500 M mimosine to extracts of MCF-7 cells cultured in the absence of mimosine does not result in decreased SHMT activity, confirming previous studies that mimosine does not inhibit SHMT activity in vitro (13). Therefore, although mimosine does decrease total SHMT-specific activity in MCF-7 cells exposed to mimosine, the decrease in SHMT activity is not directly due to the inhibition of the cSHMT enzyme activity.…”
Section: Mimosine Targets Tumor Cell Lines With Specificity-sev-supporting
confidence: 72%
See 3 more Smart Citations
“…We estimate that the cSHMT protein accounts for approximately 25% of the total SHMT activity in MCF-7 cells. 3 The addition of 500 M mimosine to extracts of MCF-7 cells cultured in the absence of mimosine does not result in decreased SHMT activity, confirming previous studies that mimosine does not inhibit SHMT activity in vitro (13). Therefore, although mimosine does decrease total SHMT-specific activity in MCF-7 cells exposed to mimosine, the decrease in SHMT activity is not directly due to the inhibition of the cSHMT enzyme activity.…”
Section: Mimosine Targets Tumor Cell Lines With Specificity-sev-supporting
confidence: 72%
“…eral studies have suggested that mimosine inhibits cell cycle progression by depleting purine deoxyribonucleotide pools through the inhibition of the folate-dependent enzyme SHMT (13). Previously, we have characterized folate metabolism in both cultured human MCF-7 cells and SH-SY5Y neuroblastoma (16,22) and have used these cell lines to study the role of SHMT in folate metabolism.…”
Section: Mimosine Targets Tumor Cell Lines With Specificity-sev-mentioning
confidence: 99%
See 2 more Smart Citations
“…The cytoplasmic serine hydroxymethyltransferase enzyme (CSHMT) catalyzes the tetrahydrofolate-dependent conversion of serine to glycine, a reaction that generates folate-activated one-carbon units that are required for purine, thymidine, and methionine biosynthesis (13). Therefore, it has been proposed that mimosine may impair deoxyribonucleotide biosynthesis by inhibiting CSHMT and ribonucleotide reductase (5,14). Other studies demonstrate that mimosine disrupts the initiation phase of DNA replication at the origins of replication in Chinese hamster ovary cells.…”
mentioning
confidence: 99%